A new genus of oribatid mite, Spineremaeus gen. nov. and three new species of Scapheremaeus (Acari: Oribatida: Cymbaeremaeidae) from Norfolk Island,South-west Pacific, and their biogeographical affinities - Colloff, Matthew J. (Zootaxa, 2011)
A new genus of oribatid mite, Spineremaeus is erected and its type species, S. smithi sp. nov., is described from Norfolk Island, as well as three new species belonging to the genus Scapheremaeus. Spineremaeus is morphologically closest to the Emarginatus species-group of Scapheremaeus, found in Australia, Java and New Zealand. Scapheremaeus pinguis sp. nov. is closest morphologically to S. emarginatus from New Zealand. Scapheremaeus pacificus sp. nov. and S. tumidus sp. nov., members of the Carinatus species-group, are closest morphologically to each other and to S. insularis, also from New Zealand. Thus all four cymbaeremaeid species from Norfolk Island show strongest biogeographical affinities with the oribatid fauna of New Zealand rather than Australia.